GOD-TALK AS A MEANS OF HEALING A Spiritual Rebirth through Novel Writing and Auto-Analysis - Dagmang•, Ferdinand D. (Journal of Dharma, 2012)
Candlelights is a novel based on my experiences in a monastic setting, including my own reflections gained through the novel’s writing process. The experience/re-experience of trauma (and its ‘domestication’) is one major element of the novel which served 1) as the central motif in the way I gave flesh to my own character, Kari, the protagonist, 2) as a driving force for the simple acts of making myself disposed to and in constant communion with the Divine, and 3) as a main strand that links together the following: (a) my past and present life, (b) the religious life which has a long contemplative tradition and a mystical approach to experiences of trauma, (c) the Transcendent as object of my personal quest, and (d) the potential readers and myself as the novel’s central character.